Karakteristik Permukiman Masa Bali Kuno di Bali Utara Berdasarkan Isi Prasasti dan Kajian Toponimi - I Gst. Ngr. Tara Wiguna; Ni Ketut Puji Astiti Laksmi; Hedwi Prihatmoko (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
A number old Bali inscriptions provide informations about past settlements scattered in many parts of Bali, and one of those is in northern part of the island. This research aims to reconstruct cultural history through epigraphic and toponymy studies as a foundation of historiography. Data collected through literature studies and surveys and analysed through textual criticism, both external and internal, and identification of toponyms. Data synthesis was conducted by placing toponym data found in inscriptions in the context of Old Balinese History. The result of this research shows that the characteristic of Old Bali settlements in North Bali could be differentiated into two categories, i.e. coastal area settlements and mountainous area settlements. Coastal area settlements have locational patterns that follow coastal line. These settlements have important roles in trade activites. Mountainous area settlements have mountain as their orientation, and the locational patterns are adjusted according to its mountainous topography and environment, thus its locations are scattered and tend to close to plantation or agricultural area.